Evaluación del efecto biocida de lochocarpus utilis (barbasco) como controlador de plagas … - Bernilla Angulo, Henry (2009)
The present investigation study, was carried out in the sector " Pabloyacu", located in the district and county of Moyobamba, Department of San Martin - Peru, having as general objective: to evaluate the effect biocida of Lochocarpus utilis (Barbasco) as controller of plagues in Phaseolus vulgaris (Panamito ). " The study factors were constituted by four treatments (including the witness), which consisted on different concentrations of the barbasco extract (Lochocarpus utilis): (25.00%), (50.00%), (75.00%), (0.00%). Use of the design of blocks complete aleoritizados was made in which was considered four treatments (Tl to 25%, T2 to 50%, T3 to 75% and the TO was considered as · witness and as such any dose of the barbasco concentration was not applied (Lochocarpus utilis). The treatments that were with more insecticide effect were the T2 and the T3 (with 50 and 75% of dose of barbasco extract), continued by the Tl and the TO which reached bigger levels in terms ofthe · degree of affectation. Y ou concludes that the use of barbasco extracts reduces the crisomélidas populations, to contain substances that can exercise action in repellent form and insecticide in the cultivation of organic panamito.